Effects of Inoculation, Planting Dates and Imbibition Duration on Some Agronomic Characters and Seed Yields of Soybean (Glycine max L.) - Uslu N.; Aytaç S.; Esendal E. (My University, 1997)
This study was conducted to determine the effects of inoculation, planting dates and imbibition duration on the seed yield and agronomic traits of soybean (cv. P-9292) under Bafra (Samsun) climatical condition. Four planting dates (6, 17, 27 May and 6 June) were assessed in 1993. For imbibition, the seeds were soaked in wet towels for 0, 3, 6, 12, 24 or 48 hours. Then, either inoculated (with R. japonicum) or non inoculated seeds were planted. A split-split randomized block design with three replicates was used. Emergence, flowering, pod filling and the maturity prolonged when the seeds were early planted. But at the last two planting'dates (27 May and 6 June), when the seeds were soaked for 24 and 48 hours, the emergences hastened for 2 to 3 days. The growing period of plants ranged from 124 to 113 days depending on the planting dates. The plant height, number of pod/plant, number of seed/plant, number of nodule/plant, nodule dry weight/plant and 1000 seeds weight were increased with the inoculation. However, in the last planting date, all the values for the same characters were decreased. The oil content of seed was decreased, but the protein content was increased by inoculation. The oil and protein contents of seed were 23.04 and 36.96 %, respectively, when the seeds were not inoculated. Similarly, 22.86 and 38.33 % values for oil and protein contents, respectively, were obtained when the seeds were inoculated. The effect of inoculation on the protein content was highly significant (P<0.01). The effects of planting dates on the oil and protein contents were highly significant (P<0.01), too, and the maximum oil content (23.34 %) from third planting date and the maximum protein content (38.98 %) from first planting date were taken. The seed yield was increased by inoculation and this increase was statistically significant (P<0.05). They increased from 216.8 kg/ da to 267.3 kg/da. Meanwhile, the seed yields were decreased with the late plantings. The maximum yield (279.9 kg/da) was obtained from the first planting date. One month delay of planting resulted in about 29.1 percent decreases in the seed yields. No influence of imbibition on the agronomic traits and the seed yield was found.
Bakteri Aşilamasi, Ekim Zamani ve Nemlendirme Süresinin Soya Fasulyesinin (Glycine max L.) Bitkisel Özellikleri ve Tohum Verimine Etkisi